Integrasi Multimedia Pembelajaran Interaktif Untuk Penanaman Literasi Anak Usia Dini di Kota Solo - Luthfia Karimah; Raeh Niken Baghiroh Raeh; Dewi Anggareni (Universitas Tangerang Raya, 2022)
The city of Solo is the only city in Indonesia that has a free storybook distribution program for early childhood, namely the bolokuncoro program (Solo boy diligently moco aksoro). The research objectives are: 1) Developing technology-based bolokuncoro learning media products and local wisdom for inculcating early childhood literacy culture 2) Applying technology-based bolokuncoro learning media and local wisdom for inculcating early childhood literacy culture. This research is a development research (R&D) with the ADDIE model, the results of this study are: 1) The creation of interactive multimedia learning bolokuncoro 2) The growth of early childhood literacy culture in the city of Solo through the integration of interactive multimedia learning bolokuncoro with the results of the experimental class n-gain score 0 ,84 high category and control class 0,51 medium category. Thus interactive multimedia learning is effective for instilling a culture of early childhood literacy based on local wisdom that exists in the city of Solo and with a wider scope.